Alterations in levels of DnaK and GroEL result in diminished survival and adherence of stressed Haemophilus ducreyi. - Parsons, L M (1997)
Haemophilus ducreyi is a hemin-requiring bacterium causing the genital ulcer disease chancroid. Previously we demonstrated that the heat shock protein GroEL was immunogenic and possibly highly expressed in a mammalian host. The present study was initiated to (i) determine the relative amounts of GroEL expressed by H. ducreyi during in vitro exposure to stresses and (ii) evaluate whether a high level of GroEL is directly or indirectly required for survival and adherence of stressed H. ducreyi. Using scanning densitometry of sodium dodecyl sulfate-polyacrylamide gel electrophoresis protein profiles, we found that H. ducreyi expressed high basal levels of GroEL, averaging fivefold greater than in Escherichia coli. These high GroEL levels increased up to twofold upon exposure of the organism to heat shock or high levels of hydrogen peroxide and during adherence to two human genital cell lines. Furthermore, when the gene for DnaK was present on a multicopy plasmid in H. ducreyi, a 1.8-fold increase in DnaK and a 2.3-fold reduction in GroEL were seen. These results suggest that DnaK serves as a negative modulator of H. ducreyi GroEL. Subsequently we found that H. ducreyi with lower GroEL had diminished ability to survive when challenged by heat and oxidative stresses. In addition, the long, parallel chains characteristic of virulent strains of H. ducreyi were absent when GroEL was lowered, so that fewer bacterial cells adhered to the human cells. These results suggest that the unusually high basal levels of GroEL are involved, either directly or indirectly, in the survival, chaining, and adherence of H. ducreyi in the presence of the combined stresses of the host environment.